Stereoselective Synthesis of Lignans of Three Structural Types from a Common Intermediate, Enantioselective Synthesis of (+)‐Yangambin. Issue 25 (21st July 2014) - Syed, Majid Khalil; Murray, Cian; Casey, Mike
Abstract: Enantioselective total synthesis of (+)‐yangambin was achieved. The key transformation is one‐pot conjugate addition/aldol reaction that involves an enantioenriched benzyl tert ‐butyl sulfoxide, an enone, and gaseous formaldehyde to construct the bis(phenylpropanoid) backbone with excellent stereoselectivity and in good yield. Reduction of the ketone with diisobutylaluminium hydride and acid‐catalysed cyclisation in EtOH furnished (+)‐yangambin in good yield. The resulting synthesis is short, efficient and highly selective. Formation of 2, 5‐diaryltetrahydrofuran lignans was observed as a side reaction in the final step of yangambin synthesis. Acid‐catalysed cyclisation of the aldol intermediate gave a completely different outcome. Dehydration to give an enone was followed by two electrophilic aromatic substitution reactions to furnish a derivative of the lignan lirionol. Abstract : Construction of a bis(phenylpropanoid) backbone through a one‐pot conjugate addition/aldol reaction. Reduction and acid‐catalysed cyclisation of the aldol intermediate gave (+)‐yangambin in good yield with 2, 5‐diaryltetrahydrofuran lignans as minor products, whereas the acid‐catalysed cyclisation of the aldol intermediate resulted in a derivative of the lignan lirionol.